Inhaled nitric oxide for high-altitude pulmonary edema - Scherrer, Urs; Vollenweider, Laurent; Delabays, Alain; Savcic, Milos; Eichenberger, Urs; Kleger, Gian-Reto; Fikrle, Antonin; Ballmer, Peter E.; Nicod, Pascal; Bärtsch, Peter (The New England journal of medicine, 1996)
High-altitude pulmonary edema is a life-threatening condition1 characterized by marked pulmonary vasoconstriction.2-6 Even though the exact underlying mechanisms of high-altitude pulmonary edema are incompletely understood, pulmonary hypertension is thought to play an important part.3,7-9 On the basis of the hypothesis that in this condition pulmonary arteriolar vasoconstriction is heterogeneous, leading to areas of hypoperfusion and hyperperfusion, a decrease in pulmonary-artery pressure may be beneficial in two ways. A reduction of capillary pressure in overperfused areas may reduce the formation of edema, whereas augmentation of perfusion in previously underperfused areas, where gas exchange is not impaired, may improve . . .